Pemberdayaan Komunitas dalam Kesehatan Mental melalui Hilirisasi Program Berbasis Asset-Based Community Development (ABCD): Muhammad Irwan1, Aco Mursid, Irfan, Al Rahman Wal Ikram, Harmawati, Risnah - Risnah, Risnah; Irwan, Muhammad; Mursid, Aco; Irfan; Harmawati; Wal Ikram, Al Rahman (PABBURA : Health Service Journal, 2025)
Mental health is a crucial aspect of improving quality of life, yet it often remains neglected at the community level due to stigma and limited access to services. This community service program aimed to enhance mental health literacy and empower residents through the Asset-Based Community Development (ABCD) approach in Pamboborang Village, West Sulawesi. The program was implemented through socialization of the ABCD concept, community asset mapping, group discussions, and the formulation of action plans based on local potential. The results indicated that the community successfully identified five categories of assets—human, social, physical, economic, and institutional—that could be utilized to support mental health. The program also contributed to reducing stigma, fostering openness among participants in sharing their experiences, and encouraging village authorities to integrate mental health into local development programs. In conclusion, the ABCD approach proved effective in strengthening community participation, mobilizing local assets, and raising collective awareness of mental health. The sustainability of this program requires strong collaboration among communities, local governments, and higher education institutions to ensure that community-based mental health initiatives are well integrated and contribute to achieving the Sustainable Development Goals (SDGs).